ROOTING OF THE PURPLE ROBE Robinia pseudoacasia L. CUTTINGS AS INFLUENCED BY CUTTING TIME, COLD STORAGE AND IBA - HAWRAMEE, OTHMAN KAMIL AREF (Journal of Duhok University, 2020)
The Purple Robe fruitless cultivar of black locust Robinia pseudoacacia L. is an attractive ornamental tree that widely planted throughout the world for various uses. This study was attempted to propagate this fruitless cultivar of Robinia by hardwood cuttings; at different cutting times, cold mist storage conditions and using various concentrations of IBA.The results showed that taking and planting cuttings on March 15th, gave the best survival percentage of rooted seedlings, which was (20.83%) compared to February 1st (8.33%) and February 22nd (12.5%).Cuttings treated with different concentrations of IBA significantly increased success percentage (38.33, 33.33, 25.00 and 14.17%) for (2000, 1500, 1000 and 0 ppm), respectively. While the cold moist storage duration of the cuttings negatively affected on survival percentage (16.67%) for 3 weeks and (12.5%) for 6 weeks storage compared to (20.83%) for non-stored cuttings. Furthermore, the treatment combination of previous factors had positive effects on studied characters; the heighest value of rooting rate success (62.5%), seedling height (82.67 cm), vegetation fresh weight (66.3 g), vegetation dry weight (21.26 g), and number of leaves per plant (32.33) were obtained from cuttings taken on February 22nd and treated with 2000 ppm, whereas the highest means of roots fresh and dry weights (12.71 and 3.62 g), respectively, were observed from cuttings taken on February 1st and treated with 2000 ppm.The results recommend taking cuttings on February 22nd, and using 2000 ppm of IBA directly (without cold moist storage) before planting to enhance cuttings survival percentage and seedlings quality